Ibf1 and Ibf2 are novel CP190‐interacting proteins required for insulator function. (6th February 2014) - Cuartero, Sergi; Fresán, Ujué; Reina, Oscar; Planet, Evarist; Espinàs, M Lluisa
Abstract Insulators are DNA‐protein complexes that play a central role in chromatin organization and regulation of gene expression. In Drosophila different proteins, dCTCF, Su(Hw), and BEAF bind to specific subsets of insulators most of them having in common CP190. It has been shown that there are a number of CP190‐binding sites that are not shared with any other known insulator protein, suggesting that other proteins could cooperate with CP190 to regulate insulator activity. Here we report on the identification of two previously uncharacterized proteins as CP190‐interacting proteins, that we have named Ibf1 and Ibf2. These proteins localize at insulator bodies and associate with chromatin at CP190‐binding sites throughout the genome. We also show that Ibf1 and Ibf2 are DNA‐binding proteins that form hetero‐oligomers that mediate CP190 binding to chromatin. Moreover, Ibf1 and Ibf2 are necessary for insulator activity in enhancer‐blocking assays and Ibf2 null mutation cause a homeotic phenotype. Taken together our data reveal a novel pathway of CP190 recruitment to chromatin that is required for insulator activity.